DESAIN INSTRUMEN PENILAIAN MATEMATIKA BERBASIS KURIKULUM EKONOMI BISNIS UNTUK PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN HUKUM PERMINTAAN DAN PENAWARAN - Rina Kurniawaty (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
Mathematics learning in SMK has a very important role. Mathematics as a science that bridges students to be able to think logically, carefully, systematically and practically in general is the orientation of vocational students so that they can be absorbed in the world of work and can develop themselves according to their productive competencies. Learning strategies are needed in such a way so that these goals can run well. This study aims to develop a design for a Mathematics assessment instrument based on the Business Economics curriculum. The development of the instrument was carried out through a research development design which was carried out through 7 stages, namely starting with needs analysis, synchronizing teaching materials, making trial instruments, implementing instruments, evaluating instrument trials, revising trials and finalizing assessment instruments.